Evaluation of the Response of HNSCC Cell Lines to γ-Rays and 12C Ions: Can Radioresistant Tumors Be Identified and Selected for 12C Ion Radiotherapy? - Ding, Lianghao; Sishc, Brock J.; Polsdofer, Elizabeth; Yordy, John S.; Facoetti, Angelica; Ciocca, Mario; Saha, Debabrata; Pompos, Arnold; Davis, Anthony J.; Story, Michael D. (Frontiers in Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide. Thirty percent of patients will experience locoregional recurrence for which median survival is less than one year. Factors contributing to treatment failure include inherent resistance to X-rays, hypoxia, epithelial to mesenchymal transition, and immune suppression. The enhanced effectiveness of 12C radiotherapy includes reduced dependence on oxygen presence, the generation of complex DNA damage, and the potential to overcome immune suppression, making it well suited for the treatment of HNSCC and particularly for radioresistant HNSCC. Clonogenic survival assays were performed on a panel of 46 HNSCC cell lines and the surviving fraction at 3.5 Gy (SF3.5) was used to rank order the panel and then Euclidean distance was used to segregate the cell lines into four groups based upon radioresistance. Gene expression analysis on untreated cells identified a molecular phenotype that distinguished the radioresistant cells from the other cell lines and a 36 gene signature was able to place cells in their respective radiosensitivity cohorts with an accuracy of 86%. Radioresistant cells were characterized by an overrepresentation of genes associated with radioresistance mechanisms including G2 checkpoint, p53 response, the unfolded protein response, apoptosis blockade, nucleotide excision repair, and known survival and proliferation pathways. Five cell lines whose SF3.5 values ranged from average to resistant, were then irradiated with 12C ions (LET 80 keV/) to determine the extent to which 12C irradiation can overcome X-ray radioresistance and to determine individual Relative Biological Effectiveness (RBE) values for each cell line using different endpoints to calculate RBE. Survival data were used in conjunction with an in silico-based modeling approach to evaluate tumor control probability based upon treatment schedules used clinically for X-rays and 12C ions where either a fixed RBE or the RBE determined for each cell line was used. Based on the above analysis, we present the framework of a strategy to utilize biological markers to predict which HNSCC patients are radioresistant and who would benefit the most from 12C radiotherapy as well as the potential limitations of generic RBE values when treating radioresistant patients with 12C ions.